Fear in the poetry of Al- Farasdaq between declaration and insinuation - El Jarboua, Ahmed Mohamed Ali (Journal of Humanities & Social Sciences, 2017)
This research highlights the phenomenon of fear in the poetry of Al-Farazdaq, nor studied wholesale in his office, but rather studied and focuses them through poetry that said the poet Ziad and pilgrims, and two of the rulers of Iraq, and had a great impact in guiding this phenomenon in Farazdaq systems , which emptied the most part two, Voolina our attention in this research near the poet of the governor and after him, and the reasons for it, and how it grew up felt the fear of Ziad and pilgrims in particular, and what the resulting poetic expression of his features and characteristics at each stage, and With each and every one, and the age of Farazdak and his age, and his vision of the policy of his time, and politicians as a champion in every experience, as he named his hair Afraid to contrast with Ziad and pilgrims, which resulted after their death quite a few of Alohadjiy came to mention some of them in this research, with different implications depending on the severity of the fear that the poet lived with this governor or that.
Keywords: poetry of fear; fear of al-Farazdaq; Ziyad and al-Hajjaj